PROPOSED PRODUCT STRATEGY BASED ON CONSUMER PREFERENCE FOR FASHION HIJAB BRAND (CASE STUDY: HUMAIRA LABEL) (The Indonesian Journal of Business Administration, 2019)
Muslim fashion industry has emerged to develop in Indonesia and considerable potential to become the center of the world's Muslim fashion according to Muslim fashion consumption estimated at US $20 billion with growth rate of 18.2 % per year in Indonesia (Global Islamic Report, 2018/2019). Humaira Label is a local brand of self manufactured Scarf and Woman Muslim Wear that aims to create modest, smart casual, exclusivity and unique scarf design with premium quality based on Bandung, established in August 2018. The raw material of Humaira Label built by natural fabrics, such as lyocell, cotton voile, miracle voile and ultrafine voile with various of beautiful unique design. The motif/design of scarves is exclusive because Humaira Label changes the design dynamically every batch. Its inspired by the lifestyle of dynamic and active working women in style - smart casual.This research aims to propose product strategy based on consumer preference by determining the cause of instability income of Humaira Label which is indicated by no sales indicate in several months by using internal and external factors analysis to find the root problems using STP, Marketing Mix Analysis, Porters Five and PEST Analysis, customer analysis and benchmark analysis and then been concluded in SWOT analysis and TOWS matrix. To know the customer preference toward hijab product, conducted the questionnaire by 103 respondents by analyzing the descriptive analysis and conjoint analysis.From matrix TOWS analysis, author proposed several alternative product strategies that can be implemented by Humaira Label. Those alternatives product strategy based on consumer preference that had been chosen to be proposed are making variance of product, improving promotion placement in social media, empowering local brand by creating brand value, reseller and drop shipper program, collaborate with social influencer in media social, and develop customer engagement program.Keywords:Muslim Fashion industry, Hijab, Product Strategy, Consumer Preference, TOWS matrix